Perceptions of Environmental Risks in Mozambique : Implications for the Success of Adaptation and Coping Strategies - Patt, Anthony G. (World Bank, Washington, DC, 2012)
Policies to promote adaptation climate risks often rely on the willing cooperation of the intended beneficiaries. If these beneficiaries disagree with policy makers and programme managers about the need for adaptation, or the effectiveness of the measures they are being asked to undertake, then implementation of the policies will fail. A case study of a resettlement programme in Mozambique shows this to be the case. Farmers and policy-maker disagreed about the seriousness of climate risks, and the potential negative consequences of proposed adaptive measures. A project to provide more information about climate change to farmers did not change their beliefs. The results highlight the need for active dialog across stakeholder groups, as a necessary condition for formulating policies that can then be successfully implemented.